Effect of matrix metalloproteinase-9 inhibitors in hepatitis B virus replication - Kalista, Kemal Fariz; Harimurti, Kuntjoro; Immanuel, Suzanna; Iskandriati, Diah; Lesmana, Cosmas Rinaldi Adithya; Ibrahim, Fera; Gani, Rino Alvani (Medical Journal of Indonesia, 2025)
BACKGROUND Hepatitis B virus (HBV) remains difficult to eradicate due to the persistence of covalently closed circular DNA (cccDNA). Matrix metalloproteinase-9 (MMP-9) enhances HBV replication, but the effects of its inhibition remain unexplored. This study aimed to investigate the effects of MMP-9 inhibitors on HBV replication markers. METHODS Primary hepatocyte cultures were obtained from the livers of 6 Tupaia javanica. Cultures were infected with HBV from human sera and divided into control and intervention groups. The intervention group received MMP-9 inhibitors at 1, 3, and 7 nM. The control group received phosphate-buffered saline. Levels of hepatitis B surface antigen (HBsAg), HBV DNA, cccDNA, MMP-9, interferon alpha and beta receptor subunit 1 (IFNAR1), and interferon beta (IFN-β) were measured in both groups before and 72 hours post-intervention. RESULTS MMP-9 inhibitor administration at 1, 3, and 7 nM consistently reduced HBsAg, HBV DNA, cccDNA, and MMP-9 levels, though not statistically significant. Median HBV DNA levels at 1, 3, and 7 nM were 7.05, 5.29, and 5.98 ×103 copies/ml, respectively. Mean cccDNA levels at 1, 3, and 7 nM were 14.15, 11.04, and 13.94 ×103 copies/ml, respectively. The 3 nM dose increased IFNAR1 levels, while the 7 nM dose increased IFN-β, but neither change was significant. Among the tested doses, 3 nM showed the most favorable effects despite the lack of significance. CONCLUSIONS MMP-9 inhibitor suppressed HBsAg, HBV DNA, cccDNA, and MMP-9 while increasing IFNAR1 and IFN-β in vitro.